answersLogoWhite

0


Best Answer

Yes because if 1+0=1 than 0 plus b equals b

User Avatar

Peja Wilson

Lvl 2
โˆ™ 2021-09-06 19:05:53
This answer is:
๐Ÿ™
2
๐Ÿคจ
1
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

1 card

What is the name of Steve on minecraft's name

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards
More answers
User Avatar

Wiki User

โˆ™ 2010-10-01 21:27:45

No it can't

User Avatar

Add your answer:

Earn +20 pts
Q: CAN 0 plus equals B plus equals B?
Write your answer...
Submit
Related questions

What is the answer to A plus B plus C equals A times B equals C?

A=0 b=0 c=0


If a plus b plus c not equal to 0 then a divided by b plus c equals b divided by c plus a equals c divided by a plus b prove that a equals b equals c?

Because there is no way to define the divisors, the equations cannot be evaluated.


Which property says that a plus b equals b plus a?

The commutative property.


Ax plus bx plus c equals 0?

x = -c/(a+b), provided a+b is not 0


What property is 0 plus b equals b?

0 is the identity element with regard to addition.


What will be the X in terms of a and b if Cos aX equals 1 plus bX and a and b are constants?

a = 0, b = 0.


If x equals a-b y equals b-c z equals c-a then the value of x plus y plus z x plus y plus z is?

x + y + z = 0 x = a - b, y = b - c, z = c - a, therefore a - b + b - c + c - a = ? a - a + b - b + c - c = 0


How do you solve a squared plus a plus ab plus b equals 0?

That factors to (a + 1)(a + b) a = -1, -b b = -a


What is a plus c-b if a equals 3 b equals 5 and c equals 2?

a + c - b = 3 + 2 - 5 = 5 - 5 = 0


How do you change y equals mx plus b to Ax plus By plus C equals 0?

Just subtract y from both sides. 'm' becomes 'A', 'b' becomes 'C' and 'B' will be equal to one.


Why is b the y-intercept in y equals mx plus b?

If x=0, then y=b on the vertical line at x=0.


If A plus B equals 0 what can you say about the components?

they are additive inverses


If a plus b equals 0 what can you say about the component?

That a and b are additive inverses of one another.


If a plus b equals c and b plus c equals d and c plus d equals e and a equals 7 and e equals 5 what is a plus b plus c plus d plus e equal?

the answer is a


What is the discriminant in the quadratic equation x to the 2nd power plus 11x plus 121 equals x plus 96 A.100 B.0 C.20 D.200?

It is B, 0.


Intercept in y equals mx plus b?

The y intercept is at co-ordinates (0,b).


What kind of equation is ax plus b equals 0 in?

A linear equation.


If a plus a equals b and b plus c equals a and a-c equals b what is c?

a= (+a) or a= (-) b= 2a b= 2a c= (-a) c= (+a)


What is b plus b plus b plus b equals?

4b


If a plus b equals 40 b plus c equals 34 and a plus c equals 42 what does b equal?

a=24 b=16 c=18


If a equals b then a plus c equals b plus c?

yes


What is greater if a equals b equals c c 0 A equals a plus b B equals c?

well if the coefficient of a times the negative reciprical of b equals 4.33 then if you add all of them they should be able to fit in as themselves int the equation: x=-b(plus or minus) (the sqare root of:(b)(b)+-4ac) all divided by 2a, the basic quadratic equation its elementery me dear lad


How do you solve the following quadratic equations with the India method A. x2-2x-13 equals 0 B. 4x2-4x plus 3 equals 0 C. x2 plus 12x-64 equals 0 D. 2x2-3x-5 equals 0?

Simply by using the formula x= -b +/- Underroot of (b2 - 4.a.c) / 2.a 2+x-6=2x+4


How do you find the y intercept in y equals mx plus b?

At the y-intercept, x=0 and y = b .


What is the simplified solution to BC plus 0 equals f?

f = B x C